Online Trolls: Unaffectionate Psychopaths or Just Lonely Outcasts and Angry Partisans? - Verbalyte, Monika (2022)
The main objective of the article is to attempt to provide a more sociological explanation of why some people attack and insult others online, i.e., considering not only their personality structure but also social and situational factors. The main theoretical dichotomy we built on is between powerful high‐status and low‐on‐empathy “bullies” trolling others for their own entertainment, and people who are socially isolated, disempowered, or politically involved, therefore feel attacked by others’ beliefs and opinions expressed online, and troll defensively or reactively instead of primarily maliciously. With an MTurk sample of over 1,000 adult respondents from the US, we tested these assumptions. We could confirm that there are two categories and motivations for trolling: for fun and more defensive/reactive. Further, we checked how strongly precarious working conditions, low social status, social isolation, and political as well as religious affiliation of the person increase or decrease the probability of trolling as well as enjoyment levels from this activity. We controlled for personality traits, social media use and patterns, as well as sociodemographic factors. We could confirm that political identities and religiosity increase the likelihood of, but not the enjoyment of trolling; however, socio‐economic factors do not have the same differentiating effect.